Effect of sub lethal exposure to copper on oxidativeStress and antioxidant defenses in catlacatla l. - GUTHA RAJASEKAR,; YARRAPPAGAARI SURESH,; BENNE LAKSHMI NARSIMHULU,; THOPIREDDY LAVANYA,; SADDALA RAJESWARA REDDY, (International Journal of Pharma and Bio Sciences, 2017)
We investigated the effect of copper exposure on antioxidant defenses and oxidative stress in fish Catla catla. Metals commonly reach to waters by natural and anthropogenic activities and can induce oxidative stress in the aquatic organisms. Fish exposed to three toxic doses of the lethal concentration 50% of Cu for 96 hours (50%, 25%, 12.5% of 96h-LC50 of Cu were 65 µg/L,130µg/L and 260µg/L, respectively).The oxidative stress response of catla with exposure to copper thus tested in present study. The activities of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), glutathione reductase (GR) and glutathione S-transferase (GST), and oxidative stress indices lipid peroxidation (LPX) and carbonyl proteins (CP) were determined after 96h of exposure to sub lethal copper concentrations in the liver, kidney, brain, intestine and gill. The changes in levels of protein carbonyls and lipid peroxidation, used as an index of oxidative stress, did not directly correlate with the antioxidant responses. The observed effects on carp antioxidant systems may be a defense against oxidative damage. Fish exposure to Cu reduced SOD activity in brain and increased its activity in liver, kidney, brain and intestine, whereas Cu exposure caused decrease of CAT activity in liver, kidney, intestine and gill but the activity in brain increased. The GPX, GR and GST either increased or remained unchanged depending on tissue-type and Cu exposure levels. This study is the first report on changes in antioxidant parameters and the importance of evaluating the potential risk of Cu to C. Catla fish at sub lethal copper concentrations.